Host-defense peptides from skin secretions of the tetraploid frogs Xenopus petersii and Xenopus pygmaeus, and the octoploid frog Xenopus lenduensis (Pipidae) - King, Jay D.; Mechkarska, Milena; Coquet, Laurent; Leprince, Jérôme; Jouenne, Thierry; Vaudry, Hubert; Takada, Koji; Conlon, J. Michael (Peptides (New York, N.Y. : 1980), 2012)
► Magainin, PGLa, and CPF peptides have been isolated from skin secretions of three Xenopus species. ► Xenopus petersii has a close but not conspecific phylogenetic relationships with Xenopus laevis. ► Xenopus pygmaeus does not belong in the laevis and muelleri species groups. ► Xenopus lenduensis expresses the full complement of four PGLa genes. ► CPF peptides show the greatest antimicrobial activity. Peptidomic analysis of norepinephrine-stimulated skin secretions led to the identification of host-defense peptides belonging to the magainin, peptide glycine-leucine-amide (PGLa), and caerulein precursor fragment (CPF) families from the tetraploid frogs, Xenopus petersii (Peters’ clawed frog) and Xenopus pygmaeus (Bouchia clawed frog), and the octoploid frog Xenopus lenduensis (Lendu Plateau clawed frog). Xenopsin-precursor fragment (XPF) peptides were not detected. The primary structures of the antimicrobial peptides from X. petersii demonstrate a close, but not conspecific relationship, with Xenopus laevis whereas the X. pygmaeus peptides show appreciable variation from previously characterized orthologs from other Xenopus species. Polyploidization events within the Xenopodinae (Silurana+Xenopus) are associated with extensive gene silencing (nonfunctionization) but unexpectedly the full complement of four PGLa paralogs were isolated from X. lenduendis secretions. Consistent with previous data, the CPF peptides showed the highest growth-inhibitory activity against bacteria with CPF-PG1 (GFGSLLGKALKIGTNLL.NH2) from X. pygmaeus combining high antimicrobial potency against Staphylococcus aureus (MIC=6μM) with relatively low hemolytic activity (LC50=145μM).